In Depth Parasitic Capacitance Analysis on GaN-HEMTs with Recessed MIS Gate - Kammeugne, Romeo Kom; Leroux, Charles; Frutuoso, Tadeu Mota; Cluzel, Jacques; Vauche, Laura; Gwoziecki, Romain; Garros, Xavier; Charles, Matthew; Bano, Edwige; Ghibaudo, Gerard (Journal of Electronics and Electrical Engineering, 2022)
In this study, parasitic coupling capacitance behavior on GaN devices with recessed MIS-gate is analysed in depth by combining experimental data, 2D-simulations, analytical calculations, and TEM imaging. This enabled to highlight the second channel formation. A new analytical model to determine the contribution of the active channel and the different coupling parasitic capacitances from a gate-to-channel capacitance Cgc curve of a GaN MIS-HEMT is proposed. This also enables the evaluation of the respective contribu-tions of all components such as the passivation layer and gate field plate capacitances in the parasitic ca-pacitance and effective gate length evaluation of GaN devices with recessed MIS gate, which could be useful for reliable parameter extraction, device modeling and optimization.